MICHAEL LÖWY, LEITOR DE LUKÁCS - Musse, Ricardo (Caderno CRH, 2019)
A reflexão sobre a trajetória intelectual e as obras de Georg Lukács no período compreendido entre 1909 e 1929 constitui parte ponderável dos primeiros escritos de Michael Löwy. O presente artigo acompanha seus comentários, destacando como seu fio condutor os conceitos de anticapitalismo romântico e reificação. MICHAEL LÖWY, READER OF LUKÁCS The reflection on the intellectual trajectory and the works of Georg Lukács in the period between 1909 and 1929 constitutes a significant part of Michael Löwy’s first writings. This article follows his comments highlighting the concepts of romantic anti-capitalism and reification as its main thread. Keywords: Michael Löwy. Georg Lukács. Romantic anti-capitalism. Reification. Marxism. MICHAEL LÖWY, LECTEUR DE LUKÁCS La réflexion sur la trajectoire intellectuelle et sur les travaux de Georg Lukács dans la période entre 1909 et 1929 constitue une partie non négligeable des premiers écrits de Michael Löwy. Cet article fait état de ses commentaires en soulignant comme principe directeur les concepts d’anticapitalisme romantique et de réification. Mots clés: Michael Löwy. Georg Lukács. Anticapitalisme romantique. Réification. Marxisme.